The Effect of Entrepreneurship Education on The Interpersonal Communication Ability of Students of SMA Negeri 1 Parigi (A Social Science and Entrepreneurship Journal, 2023)
This study's goal was to determine the overall impact ofentrepreneurship education on the students at SMA Negeri 1Parigi's interpersonal communication abilities. The issueidentified by this study is that students lack interpersonalcommunication skills, which deters them from starting theirown businesses. This research was conducted at SMA Negeri1 Parigi. This research uses descriptive quantitative andverification methods. The data collection technique in thisresearch is the questionnaire method as the main methodusinggoogle form and supported by the documentation method. Thegeneral description of entrepreneurship education is in the lowcategory with a percentage of 100%, and the generaldescription of interpersonal communication is in the mediumand high category, with a medium percentage of 17% and ahigh category of 83%. This study explains that there is an effectof entrepreneurship education on the interpersonalcommunication skills of SMA Negeri 1 Parigi students so thatHa is accepted and Ho is rejected.This is explained based onthe results of the t test with a calculated t value of 11.17 > ttable with a value of 1.99006, with a significance value of 0.000< 0.05. The results of the coefficient of determination (R2) inthis study indicate that the variable of entrepreneurshipeducation in explaining interpersonal communication is 61%.
Keywords: Entrepreneurship education; Interpersonal communication